2007
DOI: 10.1080/09663690701213701
|View full text |Cite
|
Sign up to set email alerts
|

Mr. Dithers Comes to Dinner: Telework and the merging of women's work and home domains in Canada

Abstract: Studies of home-based telework by women yield mixed results regarding the usefulness of telework in facilitating work-life balance. Most research on the social impacts of home-based telework focuses on workers-employees or self-employed-who deliberately choose that alternative work arrangement. Labour force analysts, however, predict an increase in employer-initiated teleworking. As a case study of the workforce of one large, financial-sector firm in Canada, this article considers the conditions of employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 30 publications
3
104
0
2
Order By: Relevance
“…More recently, some employers have begun to require their workers to work F 28,3/4 from home full-time (e.g. Johnson et al, 2007). How might the extent and choice of teleworking relate to the design and physical conditions of teleworkers' home workspace?…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some employers have begun to require their workers to work F 28,3/4 from home full-time (e.g. Johnson et al, 2007). How might the extent and choice of teleworking relate to the design and physical conditions of teleworkers' home workspace?…”
Section: Introductionmentioning
confidence: 99%
“…One strand of geographical work is concerned with the ways in which people reconcile the simultaneous time and energy demands of family life and workplace, such as adopting a form of the 'one-and-a-halfearner' model (Lewis, 2002, accounting for the prevalence of part-time working amongst mothers) or working non-standard shifts (outside the Fordist 9am-5pm model) (Tausig and Fenwick, 2001). New technologies enable the extensification of employment across discrete times and spaces, potentially blurring the boundaries between home and employment (Kwan, 2000;Perrons, 2003;Hyman et al, 2005;Jarvis and Pratt, 2006;Johnson et al, 2007). However, the possibilities offered by ICT in providing employment flexibility in time and space are not available to all workers.…”
Section: Citizen-workers Parents and The Boundary Between Home And Pmentioning
confidence: 99%
“…Geographical research explores the ways in which women, and mothers in particular, negotiate their complex, multiple and fluid identities within the context of local models of appropriate parenting to reconcile paid work, caring and domestic responsibilities (Holloway, 1999;McDowell, 2008). Some paid workers have eroded traditionally demarcated boundaries between the times and spaces of home and employment in order to reconcile their multiple demands, blurring boundaries between home and employment, as one sphere intrudes on the other (Hardill et al, 1997;Kwan, 2000;Perrons, 2003;Brannen, 2005;Hyman et al, 2005;Jarvis and Pratt, 2006;Johnson et al, 2007;Laegran, 2008). However, the choices that individuals can make in this regard are both enabled and constrained by moral values and norms towards parenting and employment, socio-economic context and institutional structures (Holloway, 1998;Duncan and Smith, 2003;Jarvis, 2005).…”
mentioning
confidence: 99%
“…22 Research on work-home preferences found that to separately work from home is becoming more difficult, even for those who prefer to keep the domains apart. 23 Employees are often unpaid for extra work hours at home expected by employers.…”
Section: Health-related Issuesmentioning
confidence: 99%